Stacking the coffins : influenza, war and revolution in Ireland, 1918-19 - Milne, Ida (Manchester History of Medicine, 2018)
A social history of the 1918-19 influenza pandemic's effects on an Ireland where normal patterns of life were disturbed by war and the growing separatist movement. The influenza seemed to disrupt every aspect of Irish life - culture, economics, politics, medicine and family life.